PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS SCRATCH UNTUK MENGATASI MISKONSEPSI SISWA PADA MATERI KOMPOSISI FUNGSI - Ratih Pitria Nurazizah; Eyus Sudihartinih (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
Composition of functions is a fundamental topic that is essential for students to understand; however, many still experience misconceptions regarding the order of operations and function notation. This research aims to design and develop Scratch-based interactive multimedia to address these misconceptions and to determine user responses. The research method employed is the Multimedia Development Life Cycle (MDLC), encompassing six stages: concept, design, material collecting, assembly, testing, and distribution. Research instruments included open-ended questionnaires, Likert-scale closed questionnaires, and interview guidelines involving 14 pre-service mathematics teachers for user acceptance testing. Expert validation results from both content and media experts indicated that the developed media achieved an average percentage of 98,21%, placing it in the “Very Feasible” category. These findings are supported by an average user response of 96.4% (“Very Good”) across all indicators (display, programming, material, language, interest, and usefulness). This interactive multimedia has the potential to reduce student misconceptions, although additional explanations for incorrect answers within the multimedia are required. Recommendations for further development include simplifying mathematical language, adding more in-depth problem solving features, and conducting future research on the effectiveness of multimedia for function composition material.